A Variable Gain Controller using Pole Placement Method with Changing Rider's Weight - Sin, HunSeob; Kim, ChangHwan; Cheong, SangHun (2017 14TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2017)
In this paper, we suggest a controller for the Segway to guarantee user safety by considering the different weight of riders. However, an optimal or fixed controller can cause accidents or inconvenience due to different behavior of the Segway when the weight of a rider is changed. To cope with the various change of weight, maintaining the same frequency and convergence time of the behavior important. Therefore, we change gains of the controller to sustain positions of poles, which handles the frequency and convergence time.